DEVELOPMENT MULTIFUNCTION BALL FOR SPORT AND PHYSICAL EDUCATION HEALTH EDUCATION - Hartono, Mugiyo (The Journal of Educational Development, 2013)
The aims to this research is to desain the multifungtion the ball that can fulfill the needs of basketball, volleyball and football games, The methodes are; 1) neds analysis, 2) Designing the initial product, 3) initial product; 4) Validation of expert by using experts; 5) Revision of the first products is done for the improvement of expert evaluation results; 6) Small scale test trials; 7) Revision of the second product; 8) large-scale trials; 9) Revision of the final product; 10) Deployment and implementation of results. Samples of small-scale trials use 36 elementary and junior high students, and for large-scale trials use 72 students of Elementary and Junior High Schools in Semarang City. The results of the final product are a multifunctional ball for basketball, volleyball and football with a size of 66 cm, made from sponge material PU (Poly Urhetane), a smooth non-slippery, weight of 270 grams, 0.250-0.3 bar of air pressure and has reflections of 105-115. Ball design describes characteristic of three ball, there are basketball, volleyball and football with bright and interesting colors. Conclusions in this study are a multifunctional ball with the correct specification as in the research results above, has a multifunction for basketball, volleyball and football for Elementary and Junior High School students, does not cause pain because they are light and proper size for Elementary and Secondary School students.